Analysis of Influence of Optical Glideslope Indicator Deviation on Carrier Aircraft Landing. (October 2019) - Du, Yajie; Zhao, Jianjun; Yang, Libin
Abstract: The guidance provided by the optical glideslope for the carrier's safe landing is very critical. Several optical glideslope stable modes are analyzed. And the line stability mode is chosen as the research object. In the line stability mode, the guiding principle of the optical glideslope is analyzed. Under this mode, the optical glideslope indication deviation can be represented by the offset of the "meat ball" seen by the pilot. Through simulation and calculation, the influence of different "meat ball" offsets on the landing point of the carrier aircraft can be obtained, which provides a reference for the safe landing of the carrier aircraft.